2004
DOI: 10.1002/glia.20112
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channels contribute to microglia/macrophage activation and function in EAE and MS

Abstract: Loss of axons is a major contributor to nonremitting deficits in the inflammatory demyelinating disease multiple sclerosis (MS). Based on biophysical studies showing that activity of axonal sodium channels can trigger axonal degeneration, recent studies have tested sodium channel-blocking drugs in experimental autoimmune encephalomyelitis (EAE), an animal model of MS, and have demonstrated a protective effect on axons. However, it is possible that, in addition to a direct effect on axons, sodium channel blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
195
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 239 publications
(207 citation statements)
references
References 57 publications
9
195
0
3
Order By: Relevance
“…Recently, it was demonstrated that the sodium channel antagonist lamotrigine was effective in protecting axons from exposure to NO (43) and might suppress the activation of innate immune cells, in particular microglia and their migratory activity in MS patients. However, the drug failed in clinical trials because it did not prevent brain atrophy later in disease (42,45). Nimodipine already has been demonstrated to restore cognitive function (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that the sodium channel antagonist lamotrigine was effective in protecting axons from exposure to NO (43) and might suppress the activation of innate immune cells, in particular microglia and their migratory activity in MS patients. However, the drug failed in clinical trials because it did not prevent brain atrophy later in disease (42,45). Nimodipine already has been demonstrated to restore cognitive function (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the sodium channel Na v 16 is upregulated on activated microglia and macrophages in EAE and MS. Microglia from knockout mice deficient in Na v 16 had attenuated phagocytic function (Craner et al, 2005). Persistent activation of sodium channels has been demonstrated to trigger axonal injury (Craner et al, 2004).…”
Section: Do Other Factors Cause Inflammation And/or Neurodegenerationmentioning
confidence: 99%
“…NaV1.6 has a less clear functional role in macrophages. Unlike NaV1.5, NaV1.6 is also expressed in unprimed human macrophages and in unprimed and primed mouse macrophages and microglia (7,8). Many invasive neoplastic cell lines also express voltage-gated sodium channels, which may regulate their ability to metastasize (9).…”
mentioning
confidence: 99%